Handbook of chronic fatigue syndrome (Wiley, 2003)
The Handbook of Chronic Fatigue Syndrome, edited by Leonard A. Jason, Patricia A. Fennell, and Renee R. Taylor, is fairly well written to cover all aspects of CFS...[It] has extensive information and excellent references. It is not only an excellent source of information on CFS, but also an excellent reference book on CFS for individuals who are diagnosing or treating this illness or are planning to enter this field....overall the balance is very fair and comprehensive. In addition, a strength of the book is that it presents a variety of different non-pharmacological intervention approaches, which include the more traditional cognitive behavioral interventions from Europe, to more stress inoculation interventions...cognitive coping efforts...non-aerobic exercise programs...comprehensive rehabilitation approaches...phase based interventions...empowerment oriented approaches... and energy envelope treatment approaches.... In my opinion, the handbook is an excellent reference book for medical libraries, medical schools, practicing physicians, heathcare providers, and others. Dharam V. Ablashi, DVM, MS, Dip. Bact., President, American Association for Chronic Fatigue Syndrome